Literature Study: Analysis of Gratitude Factors in Individuals - Abd. Hamid Cholili; Alifah Aulia Putri Difayanti; Evin Yusmafati (International Journal of Islamic Thought and Humanities, 2023)
The research aims to determine the influencing factors of gratitude in individuals as human beings. This research uses the literature study method to look for aspects that influence gratitude in individuals, using a data accumulation scheme through Google Scholar and Science Direct to access journals and scientific papers. A literature search was carried out with the keywords "gratitude", "grateful", or "grateful" with a vulnerability of 2013–2023. Keywords are chosen because the theme is related to the topic and are vulnerable to the last 10 years to get relevant and up-to-date data. Based on the search, 2,350 articles were found with the type of research article, and only the 10 most relevant articles were selected. The results of previous research and literature studies explain that the factors of gratitude in individuals consist of self-acceptance, several aspects (knowledge, experience, social support, and spiritual conditions), a sense of appreciation, good intentions, and a tendency to act positively.